An experimental proposal for electricity using the Arduino prototyping board for teaching physics - Coutinho Júnior, Antônio de Lisboa (2021)
The use of Arduino in physics laboratories is growing every year, as it is a small, functional device, with a reasonably low cost and easy access. In this article, we propose a suggestion for the teaching of Electricity, which understand the concepts of the association of resistors: series, parallel and mixed, in a practical way. Using the programmable Arduino prototyping board, as an emulator of a digital Ohmmeter. Through the developed instrument it is possible to acquire data as well as the development of a series of experiments, serving as an alternative to existing measurement instruments in schools and educational institutions, establishing a close relationship between physics and programming. The suggestion can be expanded and implemented for other measuring instruments, as well as explored in collaborative activity between students and didactic projects.